Atlas of the World: Thirtieth Edition. (USA Oxford University Press, 2023)
Oxford Atlas of the World Thirtieth Edition features crisp, clear cartography of urban areas and natural landscapes around the globe, comprehensively updated with the latest names, boundaries, sites, and features of the built environment. Twenty-two pages of stunning satellite images specially sourced and processed for this atlas, including new full-page images of Cape Town, Chennai, Hong Kong, Kansas City, Mt. Kilimanjaro, Stockholm, Thimphu, and Warsaw. Diverse thematic section exploring global topics such as climate change, conflict and cooperation, employment, migration, seasons, standards of living, trade, travel and tourism, and wealth. World statistics including population figures for all independent countries and the world's largest cities, updated using the most recent data available, as well as a new two-page feature on physical dimensions with the world's longest rivers, highest peaks, and deepest oceans. New six-page feature on global biodiversity, charting the complexity of life on earth, the impact of humans on habitats and species, and efforts to preserve life in all its variety. Updated charts and data on current topics such as inequality, inflation, globalization, public health, and urbanization. 110 detailed plans of major world cities, updated to show new transportation networks and places of interest. Thoroughly updated Gazetteer of Nations that features the latest statistics, flags, and concise political and economic summaries for the world's countries and major territories. A complete index of over 86,000 cities and towns, historical names, and geographical features with full latitude and longitude coordinates along with letter-figure grid references.
Foreword -- User Guide -- World Statistics -- Special Feature -- Images of Earth -- Gazettteer of Nations -- World Geography -- World Cities -- World Maps: The World -- Europe -- Asia -- Africa -- Australia and Oceania -- North America -- South America -- Geographical Glossary -- Index to World Maps.
115058